Investigasi Peran Aspek Keamanan Sebagai Pemoderasi Terhadap Kepuasan Pengguna Bukalapak di Jakarta - Eko Retno Indriyarti; Michael Christian; Retno Sari Murtiningsih; Nico Lukito (Politeknik Piksi Ganesha Indonesia, 2023)
This study was inspired by the intense competition in the e-commerce sector, particularly in the marketplace. People's marketplace preferences can shift at any time. As a result, the marketplace must continue to comprehend and capture the factors that influence user satisfaction. As a result, the goal of this study is to investigate the factors that influence Bukalapak's user satisfaction. PLS-SEM with SmartPLS 3.0 is used to analyze 110 Jakarta-based samples in this quantitative study. This study found that system quality and security have a significant impact on user satisfaction. In this study, access to information on the marketplace website is considered common and used to the point where it no longer has a significant impact on users. Aspects that are considered normal and common for marketplace users are used by businesses to develop other marketing strategies so that their users can still find a place.